Optimalisasi Kinerja Excavator melalui Penambahan Alat Bantu dalam Kegiatan Normalisasi Sungai Bersama Mahasiswa Magang Dinas PUPR - Sholahudinwachid, Sholahudinwachid; Rayhansyah, Galih; Usman, Mualifi; Kusumaningrum, Ira; Fakhrurozi, M. (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
River normalization activities in Jombang Regency by the Public Works and Spatial Planning Office (PUPR) aim to prevent flooding caused by sedimentation and channel narrowing. In practice, excavators often experience decreased performance in the swing component due to the accumulation of mud and dredged materials. This issue reduces work efficiency and increases operational time and costs. Through an internship program, students from Darul Ulum University Jombang designed a swing excavator cleaning tool as a technical solution. The methods included problem identification, tool design, fabrication, and field testing. The results show that the tool significantly reduces material buildup, improves swing movement, and speeds up the cleaning process without requiring long work stoppages. Therefore, this tool enhances the effectiveness and efficiency of excavator operations in river normalization activities and supports flood control efforts, while also demonstrating the tangible contribution of students in community service.